2013
DOI: 10.5301/ejo.5000277
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Zonal Analysis of Corneal Surface Temperature in Young Healthy Adults

Abstract: In healthy subjects, corneal surface temperature does not change diurnally and is warmer nasally than centrally and temporally during the interblinking interval. Our study leads to the assumption that diurnal changes of corneal temperature indicate ocular surface abnormality or corneal pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
3
1
1
Order By: Relevance
“…As previously reported, our data confirm that CT varies in response to tear film evaporation rate, which in turn is influenced by environmental temperature and blinking rate [ 19 , 42 – 44 ]. However, our results also show a peculiar pattern of CT distribution across the corneal surface, not in line with previous findings [ 12 , 14 , 15 , 45 ]. In fact, in all experimental settings (basal, after CET, and cm-CET), we detected the coolest area at the corneal temporal region while the warmest area was at the nasal side.…”
Section: Discussionsupporting
confidence: 72%
“…As previously reported, our data confirm that CT varies in response to tear film evaporation rate, which in turn is influenced by environmental temperature and blinking rate [ 19 , 42 – 44 ]. However, our results also show a peculiar pattern of CT distribution across the corneal surface, not in line with previous findings [ 12 , 14 , 15 , 45 ]. In fact, in all experimental settings (basal, after CET, and cm-CET), we detected the coolest area at the corneal temporal region while the warmest area was at the nasal side.…”
Section: Discussionsupporting
confidence: 72%
“…In our study population we could not confirm any correlation between anterior chamber depth and OST, and in the literature we find some contradictory reports about a potential correlation of anterior chamber depth and OST [29,30]. In our previous study we already could exclude a diurnal variation of OST [33].…”
Section: Discussioncontrasting
confidence: 78%
“…Measurements of ocular surface temperature 10 seconds after eye opening may prove to be a repeatable, quantifiable measurement for dry eyes but further multicenter trials need to be performed. It was recently found that corneal surface temperature does not change diurnally in healthy subjects 92. This leads to the assumption that diurnal changes in corneal temperature may indicate ocular surface abnormality or corneal pathology.…”
Section: Emerging Technologies For Diagnosismentioning
confidence: 99%